Racial/Ethnic Disparities and Culturally Competent Health Care Among Youth and Young Men - Dzung X. Vo MD; M. Jane Park MPH (American Journal of Men's Health, 2008)
Racial/ethnic disparities in health and health care are receiving increasing national attention from the fields of public health and medicine. Efforts to reduce disparities should adopt a life-span approach and recognize the role of gender. During adolescence, young people make increasingly independent decisions about health-related behavior and health care, while developing gender identity. Little is known about how cultural context shapes gender identity and gender identity's influence on health-related behavior and health care utilization. The authors review disparities in health status and health care among adolescents, especially young men, by reviewing health care access, clinical services, and issues related to culture, identity, and acculturation. Significant differences in health status by gender exist in adolescence, with young men faring worse on many health markers. This article discusses gaps in research and offers recommendations for improving health care quality and strengthening the research base on gender and disparities during adolescence.